Jeepers Reapers! - Oppy, Graham (AGATHEOS – European Journal for Philosophy of Religion, 2025)
I begin by discussing two scenarios involving independent light bulbs. I then consider extensions of these scenarios in which the states of light bulbs depend upon the states of other light bulbs. Given the discussion of these various scenarios, I argue that there is a challenging question for those who wish to make use of patchwork principles: if the scenarios that we duplicate involve successful execution of dispositions, can there be failure of execution of those dispositions in the patchworked scenarios? In the last two parts of the paper, I apply the earlier discussion to the argument against bounded non-well-founded sequences of time intervals given in Koons (2014), and to the argument against causal finitism given in Pruss (2018).